A Micromechanically-motivated Phenomenological Model for Predicting Ductile Fracture Initiation. (2017) - Mu, Lei; Zang, Yong; Li, Xiao Long; Araujo Stemler, Pedro Malaquias
Abstract: A phenomenological ductile fracture initiation model is developed based on the assumption that onset of fracture is a limit state of void evolution followed by void coalescence at microscopic level. In the model, void grows in two typical deformation modes: a) void dilation and b) void elongation/rotation. The fracture initiation model is transformed from stress space into the space of equivalent plastic strain, stress triaxiality and Lode parameter. A parametric study is carried out to better understand the effects of model parameters. The comparison with the experimental data (DP590, TRIP690, 5083-O aluminum alloy) shows a good prediction capability of the proposed model in a large range of stress state for various materials.